The other side of silence - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2016)
"Being a Berlin cop in 1942 was a little like putting down mousetraps in a cage full of tigers. The war is over. Bernie Gunther, our sardonic former Berlin homicide detective and unwilling SS officer, is now living on the French Riviera. It is 1956 and Bernie is the go-to guy at the Grand-Hotel du Cap-Ferrat, the man you turn to for touring tips or if you need a fourth for bridge. As it happens, a local writer needs just that, someone to fill the fourth seat in a regular game that is the usual evening diversion at the Villa Mauresque. Not just any writer. Perhaps the richest and most famous living writer in the world: W. Somerset Maugham. And it turns out it is not just a bridge partner that he needs; it's some professional advice. Maugham is being blackmailed--perhaps because of his unorthodox lifestyle. Or perhaps because of something in his past, because once upon a time, Maugham worked for the British secret service, and the people now blackmailing him are spies."--